2022
DOI: 10.1021/acsaelm.2c00199
|View full text |Cite
|
Sign up to set email alerts
|

Printing Nanostructured Copper for Electromagnetic Interference Shielding

Abstract: Printing metallic nanomaterials toward electromagnetic interference shielding is highly desirable, especially with a minimal thickness and mechanical flexibility. Here, we report the geometry and conductivity effects of printed nanostructured copper on the reflection and absorption of electromagnetic interference shielding. The electromagnetic interference shielding is observed to increase as the conductivity increases with the optimum electromagnetic interference shielding effectiveness of 65 dB, on which a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…As a result of the layer-by-layer assembly of the Cu nanosheets (Cu NSs), the hierarchically porous Cu film exhibited EMI SE values of 100 and 60.7 dB at 15 and 1.6 šœ‡m thickness, respectively, proving that the hierarchical internal structure of the porous Cu film and multiple interactions of incident EM waves resulted in robust radiation absorption, and suggesting a way forward for the design of EMI shielding. Similarly, Sheng et al [41] reported on EMI shielding efficiencies of printed Cu nanomaterials with the control of its conduc- tivities and nanostructured. By increasing the electronic conductivity of the printed Cu film, optimal EMI SE was found to be 65 dB.…”
Section: Metallic Materials For Emi Shieldingmentioning
confidence: 96%
See 2 more Smart Citations
“…As a result of the layer-by-layer assembly of the Cu nanosheets (Cu NSs), the hierarchically porous Cu film exhibited EMI SE values of 100 and 60.7 dB at 15 and 1.6 šœ‡m thickness, respectively, proving that the hierarchical internal structure of the porous Cu film and multiple interactions of incident EM waves resulted in robust radiation absorption, and suggesting a way forward for the design of EMI shielding. Similarly, Sheng et al [41] reported on EMI shielding efficiencies of printed Cu nanomaterials with the control of its conduc- tivities and nanostructured. By increasing the electronic conductivity of the printed Cu film, optimal EMI SE was found to be 65 dB.…”
Section: Metallic Materials For Emi Shieldingmentioning
confidence: 96%
“…It is well known that the most important factor to improve EMI shielding performance is the electrical conductivity of the core materials [17]. Several recent studies reveal that the internal structure of EMI shielding film is a critical variable modulating the shielding properties [2,40,41]. Because conductive nanomaterials have different dimensions and shapes, they form various internal structures and geometrical shapes when processed into films.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conductive fillers are key raw materials for the preparation of conductive rubber, conductive paint, etc. āˆ’ It is widely used in conductive, antistatic, and especially electromagnetic interference (EMI) shielding. Today, massive electromagnetic (EM) waves will not only cause harm to the human body but also interfere with the normal operation of electronic equipment. āˆ’ However, the water vapor at high altitudes and above the sea may cause aircraft and vessels to suffer from the salt fog environment, leading to the failure of EMI shielding materials and posing a great threat to safety. Therefore, EMI shielding materials with high salt spray resistance are still an important research topic at present. āˆ’ …”
Section: Introductionmentioning
confidence: 99%
“…Metals 3,4 and metal oxides [5][6][7] are widely used as conventional EMI shielding materials. However, the application of such materials can be limited by their high density, poor corrosion resistance and processing difficulties.…”
Section: Introductionmentioning
confidence: 99%